Planting seeds of community-engaged pedagogy: Community health nursing practice in an intergenerational campus-community gardening program. (February 2021) - Jakubec, Sonya L.; Szabo, Joanna; Gleeson, Judy; Currie, Genevieve; Flessati, Sonya
Abstract: As part of a participatory action research (PAR) study, nursing student participants collaborated with faculty, along with older adults, people with mixed abilities, and preschool aged children in order to 'sow the seeds of social change' and grow a campus community gardening project. The focus of this article is on the community-engaged pedagogy within a community health nursing practice course that supported student learning. Insights were gleaned over the course of four academic semesters (and four student cohort groups) with students as co-developers of the campus-community garden and participants in the PAR. Key themes emerged from student participants in the PAR process including: (1) planning in community to "think global, act local"; (2) discovering 'the people in your neighbourhood' as socially just partnerships; (3) revisiting landscapes of social inclusion; and (4) reflecting on "humble togetherness" across generational gaps. The findings showcased here attest to how community-engaged pedagogy, in conjunction with PAR, can facilitate student learning outside of traditional settings and grow social inclusion, intergenerational connection, and social justice. Highlights: Participatory action research and a campus-community garden combine for a deep and sustained community-engaged pedagogy. Focusing on ecohealth and social justice, community health nursing practice can flourish in a campus-community garden. In community-engaged learning with older adults, students experience how social determinants and social justice influence community health.